CRISPR-Cas-Led Revolution in Diagnosis and Management of Emerging Plant Viruses: New Avenues Toward Food and Nutritional Security - Sharma, Susheel Kumar; Gupta, Om Prakash; Pathaw, Neeta; Sharma, Devender; Maibam, Albert; Sharma, Parul; Sanasam, Jyotsana; Karkute, Suhas Gorakh; Kumar, Sandeep; Bhattacharjee, Bijoya (Frontiers in Nutrition, 2021)
Plant viruses pose a serious threat to agricultural production system worldwide. The world's population is expected to reach the 10 billion mark by 2057. Under the scenario of declining cultivable land and challenges posed by rapidly emerging and re-emerging plant pathogens, conventional strategies could not accomplish the target of keeping pace with increasing global food demand. The gene-editing techniques have recently come up as promising options to enable precise changes in genomes with greater efficiency to achieve the target of higher crop productivity. Of the genome engineering tools, clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein (Cas) have gained much popularity owing to its simplicity, reproducibility and applicability in a wide range of species. Also, the application of different Cas proteins like Cas12a, Cas13a and Cas9 nucleases have enabled the development of more robust strategies to engineer antiviral mechanisms in many plant species. Recent studies have revealed the use of various CRISPR-Cas systems to either directly target the viral gene or modify the host genome to develop viral resistance in plants. This review provides a comprehensive record of the use of the CRISPR-Cas system in the development of antiviral resistance in plants and discusses its applications in the overall enhancement of productivity and nutritional landscape of cultivated plant species. Further, the utility of this technique for the detection of various plant viruses could enable affordable and precise in-field or on-site detection. The futuristic potential of CRISPR-Cas technologies and possible challenges with its use and application are highlighted. Finally, the future of CRISPR-Cas in sustainable management of viral diseases, its practical utility and regulatory guidelines in different parts of the globe are discussed systematically.